La cara oculta de la globalización - Mejia Marcatinco, Luis (2013)
On having read the big means of the written press, or to listen to the representatives of the transnational corporations or to the neoliberal national or foreign ideologists, it(he,she) puts in evidence on a message that repeats itself with monotony hipnotizante: the world is changing hands of the technology and this change he(she) rushed at our heads with the unrestrained force of an earthquake. It is the irresistible force of the globalization of the world economy.